Epidemiological Profile of Exogenous Drug Intoxication in Brasília - Soares, Jéssica Yohanna Silva; Lima, Beatriz Matos de; Verri, Igor Araújo; Oliveira, Stefan Vilges de (Journal of Health Care, 2021)
Introduction: In Brazil, exogenous intoxications are extremely relevant public healthproblems, since they have a high frequency and morbidity in the general population of thecountry. Aim: To describe effective intervention measures to reduce cases and deaths fromdrug exogenous intoxication based on the epidemiological profile of these intoxications in thecity of Brasilia-DF. Method: an epidemiological, descriptive study, where data from theInformation System for Notifiable Diseases were analyzed, referring to the city of Brasilia-DF,including the reported cases of exogenous drug intoxication in the period from 2011 to 2017,were analyzed. To support the discussion and the intervention proposal, a literature review wascarried out on Scielo and LILACS databases. Results: 22 publications were selected afterapplying the analysis criteria and served as the basis for the intervention proposal of this article.Conclusion: We note the importance of strategies such as the promotion of quality of life,education, protection, recovery for the prevention of suicide, implementation of childprotection medication packaging, among other intervention strategie
Keywords: epidemiological monitoring; pharmaceutical preparations; toxicology; poisoning; Projects